Broadening the concept of patient safety culture through value-based healthcare. Issue 5 (2nd March 2021) - Dombrádi, Viktor; Bíró, Klára; Jonitz, Guenther; Gray, Muir; Jani, Anant
Abstract : Purpose: Decision-makers are looking for innovative approaches to improve patient experience and outcomes with the finite resources available in healthcare. The concept of value-based healthcare has been proposed as one such approach. Since unsafe care hinders patient experience and contributes to waste, the purpose of this paper is to investigate how the value-based approach can help broaden the existing concept of patient safety culture and thus, improve patient safety and healthcare value. Design/methodology/approach: In the arguments, the authors use the triple value model which consists of personal, technical and allocative value. These three aspects together promote healthcare in which the experience of care is improved through the involvement of patients, while also considering the optimal utilisation and allocation of finite healthcare resources. Findings: While the idea that patient involvement should be integrated into patient safety culture has already been suggested, there is a lack of emphasis that economic considerations can play an important role as well. Patient safety should be perceived as an investment, thus, relevant questions need to be addressed such as how much resources should be invested into patient safety, how the finite resources should be allocated to maximise health benefits at a population level and how resources should be utilised to get the best cost-benefit ratio. Originality/value: Thus far, both the importance of patient safety culture and value-based healthcare have been advocated; this paper emphasizes the need to consider these two approaches together.